Development and testing of a pineapple peeler, corer cum slicer - BINDHU K. GEORGE; Bindu Kochugovindan; Vidhu K. P; Er. Prince M. V (Guide) (Tavanur 1999 Department of Post-Harvest Technology and Agricultural Processing)
Development and testing of a pineapple peeler, corer cum slicer
Development and testing of a pineapple peeler, corer cum slicer